2012
DOI: 10.1108/10610421211215553
|View full text |Cite
|
Sign up to set email alerts
|

Consumer reaction to new package design

Abstract: PurposeThis study aims to explore the reaction of consumers to a new package design through differing levels of experience. It examines how consumers' expectation of product quality change as the consumer's experience with the package moves from indirect to direct.Design/methodology/approachRespondents evaluated a new package design at indirect, moderately direct, and direct levels of experience. Factor analysis was also conducted to determine what dimensions consumers use for evaluation.FindingsThis study rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 36 publications
4
34
0
Order By: Relevance
“…Package-ease of handle is defined as the extent to which consumers can store or handle products and prevent them from damage or breakage. In [11], it is concluded that this dimension does not have any significant associations with purchase intention under any types of consumer experience. However, when consumers are able to touch or use the product, it is more important [11].…”
Section: A Product Packaging Elementsmentioning
confidence: 89%
See 3 more Smart Citations
“…Package-ease of handle is defined as the extent to which consumers can store or handle products and prevent them from damage or breakage. In [11], it is concluded that this dimension does not have any significant associations with purchase intention under any types of consumer experience. However, when consumers are able to touch or use the product, it is more important [11].…”
Section: A Product Packaging Elementsmentioning
confidence: 89%
“…"A good packaging is far more than a salesman, it is a flag of recognition and a symbol of values" [9]. In this research, product packaging combines: visual (color, picture, font, shape and size), informational factor (packaging material and product information) [10], and package-ease of use and -ease of handle [11].…”
Section: A Product Packaging Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quality evaluation of a product is usually made by consumers when they look at the product package on the shelf. Holmes and Paswan (2012) investigate the relation of consumer make quality assumption of the product based on its product package, the higher the quality of the packaging, the higher the quality of the product and vice versa. Materials that used in packaging not only creates the quality assumption, it also play an important role that helps maintain the quality of the product especially freshness of products during the process of distribution and storage.…”
Section: H4: the Packaging Shape Has A Significant Relationship With mentioning
confidence: 99%